Anti-Doping - Jelkmann W (Deutsche Zeitschrift für Sportmedizin, 2016)
Blood doping means the use of certain techniques and/or substances to increase red blood cell (RBC) mass, which allows the body to transport more O2 to muscles and therefore increase performance.Artificial O2 carriers do not appear relevant in sports. Infused allogeneic blood is detectable, due to different blood groups, whereas re-transfused autologous blood is not. Recombinant human erythropoietin (rhEpo) and its analogs can be detected by isoelectric focusing and immunoblotting. There are peptidic Epo-mimetics, but none of these is clinically approved. The expression of the Epo gene (EPO) is stimulated by hypoxia-inducible transcription factors (HIFs), which consist of - and -subunits. Hydroxylation of the O2-labile -subunits can be prevented by the oral intake of cobaltous (Co2+) salts or -ketoglutarate competitors (HIF-stabilizers). Also conceivable is the misuse of inhibitors of the GATA binding transcription factors in order to activate the EPO promoter. EPO transfer is probably not widespread in sports.The World Anti-Doping Agency (WADA) has implemented the Athlete Biological Passport (ABP) Operating Guidelines for individual and longitudinal monitoring of several erythrocyte parameters (e.g. hemoglobin concentration [Hb], hematocritin 2009, RBC count, reticulocyte numbers [Ret], mean corpuscular RBC volume [MCV] and mean corpuscular Hb mass [MCH]). Primarily [Hb] and OFF-hr score ([Hb] - 60 Ret%,normal range: 85-95)are relevant with regard to sanctioning. The merit of the ABP approach is still under investigation.KEY WORDS: Athlete Biological Passport, Erythropoietin, Hemoglobin, Hypoxia-Inducible Transcription Factors, Recombinant DNA-technology